LOW-COST HOUSING PROVISION IN NIGERIA: LESSONS FROM THE MALAYSIA EXPERIENCE - Ebekozien, Andrew; Abdul-Aziz, Abdul-Rashid; Jaafar, Mastura (Journal of Surveying, Construction and Property, 2020)
This article discusses the housing policy of two developing economies. It examines recent research findings in the light of encumbrances facing the Nigerian housing policy with an emphasis on low-cost housing (LCH) development. It also evaluates how the Malaysian Government over the years have made a good attempt to make homeownership affordable for Malaysian citizens irrespective of their income with various LCH policies and programmes that are economically feasible and technically practicable. It examines studies in the Nigerian housing sector that revealed severe scarcity, high cost of LCH, inaccessibility to housing loan, weak LCH policy, high corruption, high inflation among others. This affords insights into the Malaysian potential policy practices that could be implemented in Nigeria to address the prolonged chronic housing problem. Hence, it evaluates whether the Malaysian LCH policy can be modified and applied in the Nigerian context as possible policy measures. The article shows that the Malaysian Government sees housing provision as one of the major pillars and synergy with other constructs of welfare in line with the system embedded approach. Furthermore, this approach appears to be gaining ground and would stir-up the Nigerian Government policy-makers with poor-friendly policies so that LIEs can gain access to homes.